2020
DOI: 10.1097/ana.0000000000000695
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Hyperthermia in Traumatic Brain Injury—Relation to Intracranial Pressure Dynamics, Cerebral Energy Metabolism, and Clinical Outcome

Abstract: Background: Systemic hyperthermia is common after traumatic brain injury (TBI) and may induce secondary brain injury, although the pathophysiology is not fully understood. In this study, our aim was to determine the incidence and temporal course of hyperthermia after TBI and its relation to intracranial pressure dynamics, cerebral metabolism, and clinical outcomes.Materials and Methods: This retrospective study included 115 TBI patients. Data from systemic physiology (body temperature, blood pressure, and arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 40 publications
0
12
0
2
Order By: Relevance
“…Furthermore, lactate is a cerebral vasodilator and higher systemic levels may increase CBF ( 55 ). However, we have found that a higher arterial lactate is independently associated with a higher PRx ( 33 ), and it is possible that the corresponding increase in CBF ( 55 ) represents dysregulated hyperemia. This calls for caution in clinical TBI trials on lactate-based fluids as a way of increasing the delivery of an alternative energy fuel to the brain due to the possible negative effect of lactate on pressure autoregulation.…”
Section: Indicative Observations and Future Perspectivesmentioning
confidence: 77%
See 4 more Smart Citations
“…Furthermore, lactate is a cerebral vasodilator and higher systemic levels may increase CBF ( 55 ). However, we have found that a higher arterial lactate is independently associated with a higher PRx ( 33 ), and it is possible that the corresponding increase in CBF ( 55 ) represents dysregulated hyperemia. This calls for caution in clinical TBI trials on lactate-based fluids as a way of increasing the delivery of an alternative energy fuel to the brain due to the possible negative effect of lactate on pressure autoregulation.…”
Section: Indicative Observations and Future Perspectivesmentioning
confidence: 77%
“…This calls for caution in clinical TBI trials on lactate-based fluids as a way of increasing the delivery of an alternative energy fuel to the brain due to the possible negative effect of lactate on pressure autoregulation. Hyperthermia could induce cerebral vasodilation, and some findings support an association between a higher body temperature and a higher PRx ( 56 ), whereas other studies have found no such association ( 33 ). Arterial hypoxia also leads to cerebral vasodilation in order to increase CBF to maintain normal brain tissue oxygenation ( 57 ), whereas higher oxygen levels may increase the cerebrovascular tone.…”
Section: Indicative Observations and Future Perspectivesmentioning
confidence: 94%
See 3 more Smart Citations